The Role of Counter-Ions in Peptides-An Overview - Karol Sikora; Maciej Jaśkiewicz; Damian Neubauer; Dorian Migoń; Wojciech Kamysz (MDPI AG, 2020)
Peptides and proteins constitute a large group of molecules that play multiple functions in living organisms. In conjunction with their important role in biological processes and advances in chemical approaches of synthesis, the interest in peptide-based drugs is still growing. As the side chains of amino acids can be basic, acidic, or neutral, the peptide drugs often occur in the form of salts with different counter-ions. This review focuses on the role of counter-ions in peptides. To date, over 60 peptide-based drugs have been approved by the FDA. Based on their area of application, biological activity, and results of preliminary tests they are characterized by different counter-ions. Moreover, the impact of counter-ions on structure, physicochemical properties, and drug formulation is analyzed. Additionally, the application of salts as mobile phase additives in chromatographic analyses and analytical techniques is highlighted.